Application of Centella asiatica extract as Biostimulant on Growth of Kale (Brassica oleracea var. acephala DC) - Sherin Dien Salsabila; Suwirmen Suwirmen; Zozy Aneloi Noli (Jurnal Biologi Tropis, 2023)
Research on the effect of pegagan (Centella asiatica) extract as a biostimulant on the growth of kale plants (Brassica oleracea var. acephala DC) was conducted from April 2022 to August 2022 in the Greenhouse and Plant Physiology Laboratory, Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Andalas, Padang. This study aims to determine the effect of giving Pegagan extract as a biostimulant that can improve the quality of kale plant leaves and the concentration of Pegagan extract that can increase the growth of kale plants. The method used in this research was an experimental method with a Completely Randomized Design (CRD) with five treatments and five replicates. Treatments included the following amounts of Pegagan extract: A. (0 mg/l), B. (12.5 mg/l), C. (25 mg/l), D. (50 mg/l), and E. (100 mg/l). The results showed that several concentrations of Pegagan extract had different effects on chlorophyll a, chlorophyll b, and total chlorophyll of kale plants. However, it did not give different effects on plant growth parameters, namely plant height, number of leaves, root length, wet weight, and dry weight of kale plants. Based on the proximate analysis, the application of Pegagan extract has not been able to influence the quality of the kale plant's water, ash, fat, carbohydrate, and vitamin C. Still, it can affect kale plants' protein and crude fiber content.